2020
DOI: 10.1002/jor.24655
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index moderates the association between gait kinetics, body composition, and femoral knee cartilage characteristics

Abstract: This study compared femoral cartilage characteristics between age‐ and sex‐matched individuals with (n = 48, age = 22.8 ± 3.5 years; body mass index [BMI] = 33.1 ± 4.1 kg/m2) and without obesity (n = 48 age = 22.0 ± 2.6 years; BMI = 21.7 ± 1.7 kg/m2) and evaluated the associations between body composition, quadriceps function, and gait kinetics with femoral cartilage characteristics. Medial and lateral femoral cartilage thickness, medial:lateral thickness ratio and medial and lateral cartilage echo intensity w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…While there was no significant association of BMI and femoral cartilage thickness in a sonographic study comparing obese with nonobese patients, obese patients tended to have higher cartilage thickness values. 42 We found a significant, weakly positive association of obesity with cartilage thickness. The variations in literature above and our findings can be explained by differences in study portocol, site (femoral vs. tibial), technique of cartilage measurement, and imaging modality.…”
Section: Discussionmentioning
confidence: 52%
“…While there was no significant association of BMI and femoral cartilage thickness in a sonographic study comparing obese with nonobese patients, obese patients tended to have higher cartilage thickness values. 42 We found a significant, weakly positive association of obesity with cartilage thickness. The variations in literature above and our findings can be explained by differences in study portocol, site (femoral vs. tibial), technique of cartilage measurement, and imaging modality.…”
Section: Discussionmentioning
confidence: 52%
“…Previous muscle ultrasound investigations have corrected for echo intensity using subcutaneous fat thickness to estimate intra-muscular fat ( Young et al 2015 ). While a recent ultrasound article corrected cartilage echo intensity by subcutaneous fat thickness ( Pamukoff et al 2020 ), further studies are needed to determine the need and to establish the most effective way to correct cartilage ultrasound echo-intensity using subcutaneous fat thickness to estimate cartilage composition. This study highlights a preliminary cross-sectional association between cartilage ultrasound echo intensity and arthroscopic cartilage damage but does not provide an indication of the prognostic value of assessing cartilage ultrasound echo intensity or the natural history of longitudinal changes in cartilage ultrasound echo intensity after injury.…”
Section: Discussionmentioning
confidence: 99%
“…This highlights the need for assessments that directly quantify the magnitude and heterogeneity of the cartilage echo intensity. Since disrupted cartilage integrity ( e.g., altered cartilage composition) may occur before cartilage thickness changes ( Li and Majumdar, 2013b ), quantitative assessment of cartilage ultrasound echo intensity may be an early indicator of altered cartilage composition ( Kuroki et al 2008 ; Saarakkala et al 2012 ; Gupta et al 2014 ; Pamukoff et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…These results are consistent with past evidence of more constant KAM loading patterns 43 reported during walking in obese individuals with knee OA, characteristic of the gait patterns linked to clinical TF OA progression by Hatfield et al 19 This highlights a potential link between altered mechanics with obesity and clinical TF progression. Moreover, Pamukoff et al 45 this year found a higher echo intensity (measured through ultrasound) in medial and lateral femoral cartilage with obesity, an indication of early cartilage breakdown 46,47 . This suggests the potential inability of cartilage to accommodate higher loads by adapting structurally in those with obesity, making the joint more vulnerable to the effect of loading.…”
Section: Biomechanics and Osteoarthritis Progressionmentioning
confidence: 95%